Integrated metagenomics and metabolomics analysis illustrates the systemic impact of the gut microbiota on host metabolism after bariatric surgery. Issue 7 (24th March 2022) - Han, Yeyoung; Kim, Gihyeon; Ahn, Eunyong; Jung, Sunhee; Jung, Youngae; Kim, Yunjae; Ha, Eunyoung; Heo, Yoonseok; Ryu, Do Hyun; Park, Hansoo; Hwang, Geum‐Sook
Abstract: Aim: To explore how bariatric surgery (BS) modified the obesity‐associated gut microbiome, the host metabolome, and their interactions in obese Korean patients. Materials and Methods: Stool and fasting blood samples were obtained before and 1, 3, 6, and 12 months after BS from 52 patients enrolled in the Korean Obesity Surgical Treatment Study. We analysed the gut microbiome by 16S rRNA gene sequencing and the serum metabolome, including bile acids, by nuclear magnetic resonance spectroscopy and ultrahigh‐performance liquid chromatography/triple quadrupole mass spectrometry. Results: Stool metagenomics showed that 27 microbiota were enriched and 14 microbiota were reduced after BS, whereas the abundances and diversity of observed features were increased. The levels of branched‐chain amino acids and metabolites of energy metabolism in serum were decreased after surgery, whereas the levels of metabolites related to microbial metabolism, including dimethyl sulphone, glycine, and secondary bile acids, were increased in the serum samples. In addition, we found notable mutual associations among metabolites and gut microbiome changes attributed to BS. Conclusions: Changes in the gut microbiome community and systemic levels of amino acids and sugars were directly derived from anatomical changes in the gastrointestinal tract after BS. We hypothesized that the observed increases in microbiome‐related serum metabolites were a result of complex and indirect changes derived from BS. Ethnic‐specific environmental or genetic factors could affect Korean‐specific postmetabolic modification in obese patients who undergo BS.